2019
DOI: 10.1002/jcb.29000
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside ameliorated hypoxia‐induced tumorigenesis of BxPC‐3 cells via downregulating hypoxia‐inducible factor (HIF)‐1α and LOXL2

Abstract: Herein, we found that salidroside suppressed hypoxia‐inducible factor 1 alpha (HIF‐1α) and lysyl oxidase‐like protein 2 (LOXL2) within human pancreatic cancer BxPC‐3 cells cultured both under normoxia and hypoxia condition. To investigate the effect of salidroside on tumorigenesis of BxPC‐3 cells and whether HIF‐1α and LXCL2 were involved in this process, cells transfected with or without LOXL2 overexpression vector, were treated with 50 μg/mL of salidroside or 50 μM of KC7F2 (a HIF‐1α inhibitor) under hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The underlying mechanism of chemosensitization activity of Sal in the HeLa-ADR cell line was investigated by Western blotting. Previous studies suggest that Sal regulates hypoxia-related pathways. ,, The heterodimeric transcription factor hypoxia-inducible factor-1 (HIF-1), composed of two subunits (HIF-1α and HIF-1β), is the major regulator of hypoxia-activated genes and is known to play a key role in the progression of tumor multidrug resistance (MDR) . In this study, we found a significant increase in HIF-1α expression in the HeLa-ADR cells (Figure A), which can be attributed to the DOX resistance.…”
Section: Resultssupporting
confidence: 51%
“…The underlying mechanism of chemosensitization activity of Sal in the HeLa-ADR cell line was investigated by Western blotting. Previous studies suggest that Sal regulates hypoxia-related pathways. ,, The heterodimeric transcription factor hypoxia-inducible factor-1 (HIF-1), composed of two subunits (HIF-1α and HIF-1β), is the major regulator of hypoxia-activated genes and is known to play a key role in the progression of tumor multidrug resistance (MDR) . In this study, we found a significant increase in HIF-1α expression in the HeLa-ADR cells (Figure A), which can be attributed to the DOX resistance.…”
Section: Resultssupporting
confidence: 51%
“…The combination of DS and BAPN exerts a superior effect compared to DS or BAPN alone [ 100 ]. In addition, salidroside, a phenylpropanoid glycoside isolated from Rhodiola rosea L, down-regulates the mRNA expression level of LOX, LOXL1-4, and HIF-1α in a dose-dependent manner in pancreatic cancer cells [ 101 ]; thereby, the invasive activity of cancer cells, xenograft tumor growth, and distal metastasis can be hindered by treatment with salidroside [ 101 ]. Further studies have indicated that Escin Ia, belonging to a subclass of the saponin fraction of Aesculus chinensis Bunge fruits (SFAC), acts towards the down-regulation of LOXL2 and the inhibition of the metastatic behavior of triple-negative breast cancer in vitro and in vivo [ 102 ].…”
Section: Therapeutic Potential Of Targeting Approaches On Lox Famimentioning
confidence: 99%
“…cholaensis . The pharmacological effects of salidroside include, but not limited to, anti‐cancer (Rong et al, 2020), anti‐inflammatory (Pu et al, 2020), anti‐hypoxia (Chen, Kou, Lu, & Pu, 2020), and anti‐oxidative properties (Liu et al, 2020). Recent pieces of evidence demonstrated that salidroside has also been considered as a potential therapeutic drug for diabetes because of its beneficial action in diabetic rodent models (Feng, Liu, Gao, Geng, & Dai, 2019).…”
Section: Introductionmentioning
confidence: 99%